A novel Monash Pouch diet in patients with an ileoanal pouch is tolerable and has favorable metabolic luminal effects - Zaid S Ardalan; Chu K Yao; Kraig Green; Chris Probert; Paul A Gill; Sam Rosella; Jane G Muir; Miles P Sparrow; Peter R Gibson (JGH Open, 2023)
Abstract Aims To evaluate a whole‐food diet strategy (the Monash Pouch diet [MPD]) designed based on the interacting roles dietary factors play with pouch health. Specifically, its tolerability and acceptability, whether it achieved its dietary and metabolic goals, and the effects on symptoms and inflammation were examined. Methods In a 6‐week open‐label trial, patients with ileoanal pouches educated on the MPD were assessed regarding diet tolerability and acceptance, food intake (7‐day food diaries), pouch‐related symptoms (clinical pouchitis disease activity index), and, in 24‐h fecal samples, calprotectin, fermentative biomarkers, and volatile organic compounds (VOC). Results Of 12 patients, 6 male, mean (SD) age 55 (5) and pouch age 13 (2) years, one withdrew with partial small bowel obstruction. Tolerability was excellent in 9 (75%) and acceptance was high (81%). Targeted changes in dietary intake were achieved. Fecal branched‐ to short‐chain fatty acid ratio increased by median 60 [IQR: 11–80]% (P = 0.02). Fecal VOCs for 3 compounds were also increased, 2‐methyl‐5‐propan‐2‐ylcyclohexa‐1,3‐diene (Fold‐change [FC] 2.08), 1,3,3‐trimethyl‐2‐oxabicyclo[2.2.2]octane (FC 3.86), propan‐2‐ol (FC 2.10). All six symptomatic patients achieved symptomatic remission (P = 0.03). Fecal calprotectin at baseline was 292 [176–527] μg/g and at week 5 was 205 [148–310] μg/g (P = 0.72). Conclusion Well tolerated and accepted, the MPD achieved targeted changes in intakes and fermentation of carbohydrates relative to that of protein. There were signals of improvement in symptoms. These results indicate the need for a randomized‐controlled trial. (Trial registration: ACTRN12621000374864; https://www.anzctr.org.au/ACTRN12621000374864.aspx).